1992
DOI: 10.1111/j.1651-2227.1992.tb12099.x
|View full text |Cite
|
Sign up to set email alerts
|

Insensible water loss from the skin during phototherapy in term and preterm infants

Abstract: The rate of evaporation from the skin was measured before and during phototherapy in 10 full-term and seven preterm infants (gestational age 29-33 weeks). The method for measurement of rate of evaporation was non-invasive and was based on determination of the water vapour pressure gradient close to the skin surface. All infants were studied naked in an incubator with an ambient relative humidity of 50% and with a controlled environment with respect to temperature and air velocity. In the term infants the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 15 publications
(11 reference statements)
1
14
1
Order By: Relevance
“…IWL can be minimized by careful temperature control of the infant. On the other hand, Kjartansson et al [5] have reported unchanged surface temperature and IWL in term and preterm infants during phototherapy. Increased cutaneous vasodilatation and IWL could be caused by long UV wavelengths (360± 420 nm) [15] or by transfer of radiant energies from phototherapy lamps into heat.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…IWL can be minimized by careful temperature control of the infant. On the other hand, Kjartansson et al [5] have reported unchanged surface temperature and IWL in term and preterm infants during phototherapy. Increased cutaneous vasodilatation and IWL could be caused by long UV wavelengths (360± 420 nm) [15] or by transfer of radiant energies from phototherapy lamps into heat.…”
Section: Discussionmentioning
confidence: 96%
“…The in¯uence of vasodilatation on a newborn's thermoregulation is unclear. Previous reports have suggested that insensible water loss (IWL) may increase or decrease during phototherapy in newborn infants [5,7,13]. There are no data about the responsiveness of cutaneous blood vessels to external thermal stimuli during phototherapy.…”
Section: Introductionmentioning
confidence: 99%
“…This influences heat loss through radiation enormously. In previous studies, servocontrol on skin temperature lowered the ambient temperature of the incubator when the bank light was switched on (4,26). The use of halogen spotlights leads to smaller T amb adjustments and thus to a stable heat balance.…”
Section: Subjectsmentioning
confidence: 99%
“…The infants were born after a (mean Ϯ SD) gestational age of 30.6 Ϯ 1.6 wk (range 27-34 wk) and had a weight at birth of 1412 Ϯ 256 g (range 966 -1880 g). The Apgar score at 5 min had a median of 8 (range [3][4][5][6][7][8][9]. At the time of the measurements, the infants had a postnatal age of 5 Ϯ 3 d (range 1-11 d) and their weight had slightly diminished to 1367 Ϯ 308 g (range 1010 -2044 g).…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation